PfSR1 controls alternative splicing and steady‐state RNA levels in Plasmodium falciparum through preferential recognition of specific RNA motifs. Issue 6 (16th April 2015) - Eshar, Shiri; Altenhofen, Lindsey; Rabner, Alona; Ross, Phil; Fastman, Yair; Mandel‐Gutfreund, Yael; Karni, Rotem; Llinás, Manuel; Dzikowski, Ron
Summary P lasmodium species have evolved complex biology to adapt to different hosts and changing environments throughout their life cycle. Remarkably, these adaptations are achieved by a relatively small genome. One way by which the parasite expands its proteome is through alternative splicing (AS). We recently identified PfSR1 as a bona fide Ser/Arg‐rich (SR) protein that shuttles between the nucleus and cytoplasm and regulates AS in Plasmodium falciparum. Here we show that PfSR1 is localized adjacent to the Nuclear Pore Complex (NPC) clusters in the nucleus of early stage parasites. To identify the endogenous RNA targets of PfSR1, we adapted an inducible overexpression system for tagged PfSR1 and performed RNA immunoprecipitation followed by microarray analysis (RIP‐chip) to recover and identify the endogenous RNA targets that bind PfSR1. Bioinformatic analysis of these RNAs revealed common sequence motifs potentially recognized by PfSR1. RNA‐EMSAs show that PfSR1 preferentially binds RNA molecules containing these motifs. Interestingly, we find that PfSR1 not only regulates AS but also the steady‐state levels of mRNAs containing these motifs in vivo.